2015
DOI: 10.1089/aid.2014.0221
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Drug Resistance-Associated Mutations in Human Immunodeficiency Virus Type 1 Protease and Reverse Transcriptase Derived from Drug-Treated Indonesian Patients

Abstract: Although HIV-1 drug resistance is a major obstacle in Indonesia, information on drug resistance is limited. In this study, the viral subtype and appearance of drug resistance mutations in the HIV-1 protease (PR) and reverse transcriptase (RT) genes were determined among drug-treated, HIV-1-infected patients in Surabaya. HIV-1 patients who received antiretroviral therapy (ART) more than 2 years were randomly recruited regardless of the viral load or ART failure. Fifty-eight HIV-1 PR genes and 53 RT genes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 10 publications
7
16
0
Order By: Relevance
“…The existence of distinct subtypes and CRFs reflects the presence of a dy- namic genetic evolutionary process of the virus. The most prominent HIV-1 subtype in Bali found in the present study was CRF01_AE, which is widely prevalent throughout Southeast Asian countries including Indonesia [8,9,17]. Previous HIV-1 genotyping studies in Indonesia reported similar findings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The existence of distinct subtypes and CRFs reflects the presence of a dy- namic genetic evolutionary process of the virus. The most prominent HIV-1 subtype in Bali found in the present study was CRF01_AE, which is widely prevalent throughout Southeast Asian countries including Indonesia [8,9,17]. Previous HIV-1 genotyping studies in Indonesia reported similar findings.…”
Section: Discussionsupporting
confidence: 84%
“…Other drugs, including didanosine (ddI), etravirine (ETR), and rilpivirine (RPV), are uncommon in the country. Although ART is successful in Indonesia, the emergence of drug resistance has been reported among treatment failure cases as well as ARTnaïve individuals [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…ART regimens and the duration of treatments for study participants are shown in Table 2. ART with a combination of 3TC, AZT, and NVP was the major treatment regimen (45.3%), and 56.6% of study participants had been receiving ART for more than 3 years ( These results are consistent with our previous findings [34]; CRF01_AE was the dominant HIV-1 subtype, while the major mutations detected were M184V, K103N, and also TAMs among HIV-1-infected individuals on ART in Surabaya, Indonesia.…”
Section: 3 Appearance Of Drug Resistance-associated Mutations In Rsupporting
confidence: 89%
“…among 46 PR genes (Table 4). Drug resistance-associated minor mutations in PR genes have also been reported in other studies in Indonesia [34]. Minor mutations have been detected in the PR genes of non-B subtypes, including CRF01_AE, as natural polymorphisms [41].…”
Section: 3 Appearance Of Drug Resistance-associated Mutations In Rsupporting
confidence: 64%
See 1 more Smart Citation